The Impact of Quick Response Adoption of Payment Code on MSMEs’ Financial Performance in Indonesia - Wardhani, Ratih Anindita; Arkeman, Yandra; Ermawati, Wita Juwita (International Journal of Social Service and Research, 2023)
The COVID-19 and digitalization trends have brought changes to the way producers and consumers interact, especially in payment transactions. In Indonesia, one method of using digital payments is using a QR code standard known as the Quick Response Code Indonesian Standard (QRIS). In accepting technology, the Technology Acceptance Model (TAM) can help predict one's acceptance of technology. The purpose of this research is to see the effect of adopting QR codes for payment on the financial performance of MSMEs in Indonesia and identify the factors and indicators that influence MSMEs in adopting QRIS. There were 296 respondents, who are users and non-users of QRIS from micro businesses throughout Indonesia. Questionnaires were distributed online, and data processing used the Structural Equation Model (SEM). The results show that the intention to adopt QRIS can significantly affect the financial performance of MSMEs, which in this case relates to an increase in the number and nominal transactions, sales turnover, business cash flow, and sales records. Perceived convenience, social influence, perceived usefulness, and perceived cost have a significant effect on influencing micro businesses to use QRIS. On the other hand, perceived compatibility, trust, personal innovativeness, and moderation variable such as length of business and experience of using digital payment does not significantly affect the micro business intention of using QRIS.